Evolusi Penelitian Sertifikasi Halal: Analisis Bibliometrik terhadap Tren dan Arah Penelitian Masa Depan - Novia Sumanti; Ferri Saputra Tanjung (Forum Kerjasama Pendidikan Tinggi, 2026)
Halal certification research continues to develop in response to the growing need of the global halal industry for a transparent, credible, and technology-adaptive halal assurance system. However, studies that comprehensively map the global evolution of halal certification research remain limited. This study aims to analyze research trends, knowledge structures, dominant themes, and future research directions in halal certification studies. This research employed a bibliometric analysis approach using data obtained from the Scopus database. The dataset consisted of 170 documents published between 2016 and 2025, limited to English-language journal articles and conference papers. The data were analyzed using Biblioshiny to identify annual publication trends, the most relevant publication sources, highly cited documents, author contributions, affiliations, countries, co-occurrence networks, and thematic maps. The novelty of this study lies in its mapping of the conceptual structure and future development of halal certification research based on recent bibliometric evidence. The results indicate that publications on halal certification have increased, particularly during 2023–2025. The keyword “halal certification” emerged as the most central theme, connecting issues related to the food industry, micro, small, and medium enterprises, governance, consumer behavior, halal supply chains, traceability, and blockchain. The thematic map shows that certification systems, inspection, halal products, Indonesia, and blockchain are motor themes, whereas halal certification for micro, small, and medium enterprises, halal knowledge, and quality management remain emerging themes. This study contributes to providing a conceptual foundation for academics, governments, certification bodies, and industry actors to strengthen a more transparent, inclusive, and sustainable halal certification ecosystem.